Climate change mitigation with carbon capture: an overview (2023)
The world is at the verge of catastrophe occasioned by the effect of climate change. Drastic action needs to be taken to reverse this ugly trend. Some of the proffered solutions to global warming is the adoption of renewable energy usage and a stop of fossil fuels combustion. However, the low capacity factor and energy return has been the bane on the usage of some renewable energy sources. A leeway however, exists in the technology of removal of greenhouse gases referred to as Carbon Capture. The widely adopted method being at point source because of its high concentration favouring easier processes of removal. This technology has received increased attention over the years as evident from data for the past five years. However, this technology alone cannot guarantee atmospheric CO2 levels required to maintain global temperature rise below the 1.50C mark. Negative emission technology processes of which the Direct Air Capture (DAC) is one needs to be developed. The infancy of the DAC technology and the uncertainties that surrounds its cost still pose as challenges. The cost of removing a tonne of CO2 with DAC technology can be as high as $600, this is unsustainable and has to be drastically reduced. While it is projected that DAC technology can take out 980 Metric Tonne (MT) CO2/annum by 2050, current figures stand at 0.008 MT. It is our view that the development of solid adsorbents and the harnessing of the thermal energy inherent in the sun can be a game changer.